Growth, optical, dielectric and mechanical studies in ferroelectric bis(methyl ammonium) tetrachlorocadmate single crystal. Issue 1 (29th November 2022) - Anitha, S.; Priya, R.; Mageshwari, P.S. Latha; Das, S. Jerome
Abstract: The bis(methylammonium) tetrachlorocadmate (MAC-Cd) single crystal was synthesized using the slow evaporation solution growth technique at ambient temperature. The grown crystal is subjected to single-crystal X-ray diffraction, Fourier transform infrared spectroscopy (FTIR), UV–vis analysis, dielectric, and mechanical study. The presence of various functional groups was confirmed by FTIR spectrum. UV–Vis spectrum analysis was used to investigate the transparency of the crystal, and the cut-off wavelength was determined to be 235 nm. Detailed dielectric study was carried out to investigate the dielectric behaviour of the title crystal. The empirical formula was utilized to theoretically assess solid-state characteristics such as valence electron, plasma energy, Penn gap, and Fermi energy for MAC-Cd and estimated values were used to compute electronic polarizability. Vickers microhardness test was performed to measure mechanical stability and the effect of indentation size was investigated using various models.